SSAU Nanosatellite Project for the Navigation and Control Technologies Demonstration. (2015) - Kirillin, Alexander; Belokonov, Igor; Timbai, Ivan; Kramlikh, Andrey; Melnik, Mariya; Ustiugov, Efim; Egorov, Andrey; Shafran, Stepan
Abstract: The article describes nanosatellite SamSat-218D designed in Samara State Aerospace University. SamSat-218D is created for testing navigation and control technologies. The experimental on-board computer is additionally installed on the board, it have the elements of "intellectual control". Algorithms of experimental computer are based on the principles of ensuring survivability, can detect and parry of failures of on-board elements in flight conditions.